Impact of a Saharan dust intrusion over southern Spain on DNI estimation with sky cameras. (December 2017) - Alonso-Montesinos, J.; Barbero, J.; Polo, J.; López, G.; Ballestrín, J.; Batlles, F.J.
Abstract: To operate Central Tower Solar Power (CTSP) plants properly, solar collector systems must be able to work under varied weather conditions. Therefore, knowing the state of the atmosphere, and more specifically the level of incident radiation, is essential operational information to adapt the electricity production system to atmospheric conditions. In this work, we analyze the impact of a strong Saharan dust intrusion on the Direct normal irradiance (DNI) registered at two sites 35 km apart in southeastern Spain: the University of Almería (UAL) and the Plataforma Solar de Almería (PSA). DNI can be inputted into the European Solar Radiation Atlas (ESRA) clear sky procedure to derive Linke turbidity values, which proved to be extremely high at the UAL. By using the Simple Model of the Atmospheric Radiative Transfer of Sunshine (SMARTS) at the PSA site, AERONET data from PSA and assuming dust dominated aerosol, DNI estimations agreed strongly with the measured DNI values. At the UAL site, a SMARTS simulation of the DNI values also seemed to be compatible with dust dominated aerosol. Highlights: An outbreak dust episode was studied in the southeast Spain on February 2016. DNI values were analyzed and estimated using SMARTS code by using AOD (500 nm). The DNI was estimated using a sky cam for a clear day and for the dust episode day. Atmospheric variables were obtained using a CL51 ceilometer with LIDAR technology.